Pendidikan Kedamaian di Era Digital (Telaah Model Forgiveness dalam Psikologi Islam) - M. Suud, fitriah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
The effort to make Islam a discipline is a necessity, because the sources of knowledge in Islam are infinite. The emerging problem usually does not lie in the matter (ontological) and its value (axiological), but on the matter of how the material is presented scientifically (epistimologically) and how a normative matter is grounded to the point that it can be used by many people. Responding to the changing times of the industry revolutionized 4.0 and in this digital era where many of life's problems increasingly complex. Fights, strife, stress, and the level of frustration increases everywhere. It is demand an educational movement to return to the teachings of Islam rahmatan lil ‘alamin. The aims of this paper are to concoct a famous science material in Islam and has become a topic in positive psychology that is forgiveness as an attempt to become a reflection and practice of reconciling the soul in the digital era. Looking back at the teachings of Islam that are full of the value of peace and compassion for the whole of nature which is a manifestation of the nature of forgiveness or forgiveness. This study is qualitative and uses idealistic methods from Islamic psychology disciplines